China's mega dam - Albert, Justin; Carroll, Michael
The Three Gorges Dam on the Yangtze River in China is the largest public works project in the history of mankind. Its size, scale and potential are unprecedented in engineering history. The dam is in its final stages of completion. Join Discovery Channel cameras - granted exclusive access to the site - as they document the dramatic effect this massive construction project will have on the surrounding countryside. Temples, villages, cities and some two million people stand to be displaced by the hydroelectric monster. With the dam already producing electricity and beginning to take on water, economic and flood control benefits are becoming clear. Still, opponents point toward the loss of precious archaeological sites and environmental stress on the region. It's an insider's look at a true engineering marvel 10 years in the making - and the human and cultural ramifications that have some wondering if it's all worth it.